Plasticity of the histamine H3 receptors after acute vestibular lesion in the adult cat - Tighilet, Brahim; mourre, Christiane; Lacour, Michel (Frontiers in Integrative Neuroscience, 2014)
After unilateral vestibular neurectomy (UVN) many molecular and neurochemical mechanisms underlie the neurophysiological reorganizations occurring in the vestibular nuclei (VN) complex, as well as the behavioral recovery process. As a key regulator, the histaminergic system appears to be a likely candidate because drugs interfering with histamine (HA) neurotransmission facilitate behavioral recovery after vestibular lesion. This study aimed at analyzing the post-lesion changes of the histaminergic system by quantifying binding to histamine H3 receptors (H3R) (mediating namely histamine autoinhibition) using a histamine H3 receptor agonist ([3H]N-α−methylhistamine). Experiments were done in brain sections of control cats (N=6) and cats submitted to UVN and killed 1 (N=6) or 3 (N=6) weeks after the lesion. UVN induced a bilateral decrease in binding density of the agonist [3H]-Nα−Methylhistamine to H3R in the tuberomammillary nuclei (TMN) at one week postlesion, with a predominant down-regulation in the ipsilateral TMN. The bilateral decrease remained at the three weeks survival time and became symmetric. Concerning brainstem structures, binding density in the VN, the prepositus hypoglossi, the subdivisions of the inferior olive (IO) decreased unilaterally on the ipsilateral side at one week and bilaterally 3 weeks after UVN. Similar changes were observed in the subdivisions of the solitary nucleus (SN) only one week after the lesion. These findings indicate vestibular lesion induces plasticity of the histamine H3R, which could contribute to vestibular function recovery.